Evaluating a novel model of hepatitis B care, Hep B PAST, in the Northern Territory of Australia: results from a prospective, population-based studyResearch in context - Kelly Hosking; Paula Binks; Teresa De Santis; Phillip Merrdi Wilson; George Garambaka Gurruwiwi; Sarah Mariyalawuy Bukulatjpi; Emily Vintour-Cesar; Melita McKinnon; Peter Nihill; Tammy-Allyn Fernandes; Belinda Greenwood-Smith; Robert Batey; et al. (Elsevier, 2024)
Summary: Background: The Northern Territory (NT) has the highest prevalence of chronic hepatitis B (CHB) in Australia. The Hep B PAST program aims to improve health outcomes for people living with CHB. Methods: This mixed methods study involves First Nations peoples living in the NT. We used participatory action research principles across three steps: 1. Foundation step: establishing hepatitis B virus (HBV) status and linkage to care; 2. Capacity building: training the health workforce; 3. Supported transition to primary healthcare: implementation of the "Hub and Spoke" model and in-language resources. Analysis occurred at three time points: 1. Pre-Hep B PAST (2018); 2. Foundation step (2020); and 3. Completion of Hep B PAST (2023). Evaluation focuses on four key indicators, the number of people: 1) with documented HBV status; 2) diagnosed with CHB; 3) receiving care; and 4) receiving treatment. Findings: Hep B PAST (2018-23) reached 40,555 people. HBV status was documented in 11% (1192/10,853), 79.2% (26,075/32,915) and 90.8% (28,675/31,588) of people at pre-Hep B PAST, foundation step, and completion respectively. An estimated 99.9% (821/822) of people were diagnosed, 86.3% (709/822) engaged in care, and 24.1% (198/822) on antiviral treatment at completion. CHB prevalence in the study population is 2.6%, decreasing from 6.1% to 0.4% in the pre- and post-vaccination cohorts. Interpretation: Hep B PAST is an effective model of care. Partner health services are exceeding elimination targets. This model could enable other countries to enhance the cascade of care and work towards eliminating HBV. Funding: National Health and Medical Research Council.